2010
DOI: 10.1002/lt.21997
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long-term effects of inhaled iloprost in portopulmonary hypertension

Abstract: Portopulmonary hypertension (PoPH) is a serious condition without an established treatment. Drugs used to treat pulmonary hypertension may have detrimental effects on portal hypertension. This study was designed to assess in patients with PoPH the acute effects of inhaled iloprost (iILO) on pulmonary and hepatic hemodynamics and to evaluate the clinical outcome after 12 months of treatment. We conducted 2 separate studies. In the first one, 21 patients with PoPH were acutely tested with 2.8 lg of iILO. Pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 38 publications
0
43
0
1
Order By: Relevance
“…Patients who have an excellent response to treatment have outcomes after liver transplantation comparable to those of other transplantation candidates. 276,277 …”
Section: Recommendationmentioning
confidence: 99%
“…Patients who have an excellent response to treatment have outcomes after liver transplantation comparable to those of other transplantation candidates. 276,277 …”
Section: Recommendationmentioning
confidence: 99%
“…Another patient with severe POPH was successfully bridged to LTx with continuous intravenous iloprost and was without PAH after 2 yrs of follow-up [43]. Recently, MELGOSA et al [44] showed both acute and sustained haemodynamic and clinical improvement over a period of 12 months in POPH patients receiving inhaled iloprost. Generally, PAs are well tolerated with minimal adverse effects that include flushing, headaches and cough.…”
Section: Pah-specific Therapiesmentioning
confidence: 99%
“…8,18,[24][25][26][27] Epoprostenol binds to endothelial receptors, resulting in increased cyclic adenosine monophosphate levels in the cytosol. This leads to smooth muscle relaxation with subsequent vasodilation.…”
Section: Discussionmentioning
confidence: 99%